Evaluating LMS Usability by Integrating Nielsen and Budd Principles - Maulidati, Zuli; Meilani, Budanis Dwi; Sodik, Anwar (Politeknik Negeri Lhokseumawe, 2025)
ABSTRACTLearning Management Systems (LMS) are integral to modern education, supporting course delivery, student engagement, and administrative functions. Usability challenges often divert users’ focus from learning content to navigating system complexities. Heuristic evaluation (HE) has revealed persistent design and usability issues in LMS interfaces, such as poor error prevention and inadequate documentation. To address the usability issues in the LMS, this study aims to evaluate the usability of the classroom ITATS using a dual-framework approach: Jakob Nielsen’s Heuristics and Andy Budd’s Heuristics. This combined approach aims to identify interface flaws and enhance usability. Nielsen’s heuristics address universal usability principles, while Budd’s guidelines emphasize modern web design elements like responsiveness and visual hierarchy. The study is evaluated by novice evaluators who are the end users of LMS. Involving novice evaluators in this study reveals a fresh perspective which cannot be shown by the experts. The study revealed about 158 issues found by 23 novice evaluators. Those were found according to Nielsen’s and Budd’s HE within the average of severity rating about 2.52 and 2.51, respectively. Nielsen’s heuristics highlight core principles such as feedback, visibility, and error prevention, while Budd’s heuristics emphasize simplicity, consistency, and user enjoyment.